Pesticide knowledge and attitude among the potato growing farmers of Bangladesh and determinant factors - Hossain, Mohammad Zabed; Ferdous, Fahliza; Rayhan, Md. Israt (Frontiers in Public Health, 2024)
The study aimed to assess the extent of pesticide use among potato-growing farmers in Bangladesh and its relationship with their knowledge, attitude, and socio-demographic characteristics. Data were collected from 553 farmers using a semi-structured questionnaire through multistage random sampling. Bivariate analysis was conducted to examine the relationship between the frequency of pesticide use and various socio-demographic factors. Results showed that out of 321 different pesticide brands reported, 50.5% were registered, while 47.7% were unregistered and 1.9% were banned. Among the registered pesticides, 5.6% were highly hazardous, 24.8% were moderately hazardous, and 6.2% were slightly hazardous as per World Health Organization category. A high percentage (96%) of farmers reported using pesticides in their fields, with 16.6% applying pesticides more than five times in a cropping season. Data revealed that majority of the farmers were aware of the negative effect of pesticides on health and environment. Most farmers used hand towels (77.9%) and ordinary shirts (70.0%) to cover their bodies to avoid pesticide exposure. Inappropriate disposal of empty pesticide containers was also observed. Negative binomial regression analysis revealed significant positive associations between the frequency of pesticide application and potato productivity, rate of fertilizer application, area of land owned by farmers, and their knowledge about the negative effects of pesticides on human health. The study suggests adopting integrated pest management practices, developing pest-resistant potato varieties, ensuring safe handling practices and disposal as well as stringent enforcement of laws to mitigate pesticide externalities and hence ensure sustainability in agriculture.